Principle of Equality and Force majeure Clause: A Study of Standard Contracts in the Indonesian Government Construction Sector - Kodrat Insany Taqwim; Sarwono Hardjomuljadi; Sami'a Samian (International Journal Labs, 2025)
This research investigates the implementation of the principle of equality in force majeure clauses under Indonesian government construction standard contracts, namely those regulated by the General Conditions of Contract (SSUK). The research is based on the idea that the risk-sharing in public construction contracts is still not fair. Contracting authorities (PPK) have most of the ability to interpret the contracts, while contractors have very few options when it comes to negotiating the conditions. A normative legal method was used, which included legislative, conceptual, and case methods. The examination encompasses the Indonesian Civil Code, the Construction Services Law, the Ministry of Public Works and Housing Regulation No. 14 /2020, and foreign standards such as FIDIC. The study identified seven structural imbalances in force majeure provisions: (1) outdated risk definitions unsuitable for modern challenges like pandemics and cyber-attacks, (2) rigid and ambiguous notification procedures that disadvantage contractors, (3) disproportionate time extension calculations ignoring chain effects, (4) absence of cost compensation mechanisms for uncontrollable risks, (5) unilateral interpretation authority vested in PPK without independent review, (6) lack of transparent risk allocation matrices, and (7) slow and ineffective dispute resolution mechanisms. These findings were confirmed through Supreme Court Decision No. 2241 K/Pdt/2020, which nullified contractor sanctions for flooding-related delays. The study recommends adopting adaptive risk definitions, establishing reasonable notification procedures (28-day standard), implementing cost compensation mechanisms, creating independent adjudication bodies, developing explicit risk allocation matrices, and streamlining dispute resolution processes to achieve contractual balance and good faith principles.